HUBUNGAN ANTARA LAYANAN BIMBINGAN KONSELING DAN MOTIVASI BELAJAR SISWA - Sukatin; Indiyani; Miptahul Khairani; Niswatul Kholisah; Liza Asri Aulia; Wahyu Nopriningsih (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
This study aims to determine the relationship between guidance and counseling services and students’ learning motivation. Learning motivation is an important factor that influences students’ success in the learning process, while guidance and counseling services function as systematic assistance to help students develop their potential, overcome problems, and foster positive attitudes toward learning. This research employed a quantitative approach with a correlational method. The research subjects were students selected using a specific sampling technique. Data were collected through questionnaires on guidance and counseling services and learning motivation, and then analyzed using statistical correlation techniques. The results indicate that there is a significant relationship between guidance and counseling services and students’ learning motivation. The better the guidance and counseling services provided, the higher the students’ learning motivation. Therefore, guidance and counseling services play an important role in enhancing students’ learning motivation and should be implemented optimally in school.